The DETERMINATION OF TANNIN CONTENT OF AVOCADO (Persea americana Mill). SEED ETHANOL EXTRACT USING THE UV-VIS SPECTROPHOTOMETRY METHOD - Rahmatullah Basri (Makassar Natural Product Journal (MNPJ), 2023)
Avocado (Persea americana Mill.) is a plant that grows in most tropical and sub-tropical countries, one of which is in Indonesia. Avocado seeds (Persea americana Mill.) contain phytochemical compounds, one of which is tannin which has anti-inlammatory properties. This study aims to determine the levels of tannins in ethanol extract of avocado (Persea americana Mill.) seeds. The tannins in avocado seeds were extracted using the maceration method with 96% ethanol solvent. In the qualitative test and quantitative test, in the qualitative test using FeCl3 reagent and in the quantitative test the determination of tannin content in the ethanol extract of avocado seeds was measured using UV-Vis spectrophotometry at a wavelength of 770 nm with tannic acid as a comparison. The results showed that the average tannin content of the ethanol extract of avocado seeds at a concentration of 500 ppm was 69,237 mgTAE/g extract.